Voxel‐based morphometry reveals brain gray matter volume changes in successful dieters. Issue 9 (19th July 2016) - Honea, Robyn A.; Szabo‐Reed, Amanda N.; Lepping, Rebecca J.; Perea, Rodrigo; Breslin, Florence; Martin, Laura E.; Brooks, William M.; Donnelly, Joseph E.; Savage, Cary R.
Abstract : Objective: To compare regional brain volume predictors of percent weight loss (WL) in dieters with obesity (DwO) and in the same participants categorized as "successful" (≥7% WL) or "unsuccessful" dieters (<7% WL). Methods: DwO ( n = 72) and participants with healthy weight ( n = 22) completed a structural MRI at baseline and 3 months. All DwO participants were enrolled in a 12‐week program consisting of a reduced calorie diet, increased physical activity, and behavioral modification. SPM8‐based voxel‐based morphometry processing streams were used for measurements of regional gray (GMV) and white matter volume and longitudinal changes in volume. Correlations between WL and baseline brain volume and change in brain volume, as well as differences between groups, were then tested. Results: %WL was positively correlated with baseline GMV in right parahippocampal and orbitofrontal gyri in DwO. Successful dieters showed greater GMV loss in the left precentral gyrus and the insula compared with unsuccessful dieters. A negative correlation was found between %WL and GMV change from baseline in the left prefrontal regions. Conclusions: Findings illustrate that WL is related to volumetric changes in brain areas previously linked to interoception and food motivation.